Electronic devices - Floyd, Thomas L. (Prentice Hall, 1996)
From discrete components to linear integrated circuits, this devices text takes a strong systems approach that identifies the circuits and components within a system, and helps students see how the circuit relates to the overall system function. Floyd adopts straightforward, understandable explanations of complex concepts, and non-technical treatment of mathematics. His coverage is balanced between discrete and integrated circuits and he makes extensive use of examples to clarify complex concepts. This text features more than 900 drawings, photographs, charts, and diagrams that help visually explain concepts.